Creating a 'reverse' integrated primary and mental healthcare clinic for those with serious mental illness. Issue 5 (20th November 2015) - Maragakis, Alexandros; Siddharthan, Ragavan; RachBeisel, Jill; Snipes, Cassandra
Abstract : Individuals with serious mental illness (SMI) are more likely to experience preventable medical health issues, such as diabetes, hyperlipidemia, obesity, and cardiovascular disease, than the general population. To further compound this issue, these individuals are less likely to seek preventative medical care. These factors result in higher usage of expensive emergency care, lower quality of care, and lower life expectancy. This manuscript presents literature that examines the health disparities this population experiences, and barriers to accessing primary care. Through the identification of these barriers, we recommend that the field of family medicine work in collaboration with the field of mental health to implement 'reverse' integrated care (RIC) systems, and provide primary care services in the mental health settings. By embedding primary care practitioners in mental health settings, where individuals with SMI are more likely to present for treatment, this population may receive treatment for somatic care by experts. This not only would improve the quality of care received by patients, but would also remove the burden of managing complex somatic care from providers trained in mental health. The rationale for this RIC system, as well as training and policy reforms, are discussed.